Individual similarities and regional differences: the impact of 2015 refugee crisis on Europeans' attitudes toward immigration. Issue 5 (20th October 2022) - Peshkopia, Ridvan; Bllaca, Liri Kosovare; Lika, Jonida
ABSTRACT: Whereas the extant literature has found similarities in attitudes toward immigration to Europe, there is less attention on European East–West attitudinal differences on immigration. We account for attitude variations brought about by the 2015 Europe's refugee crisis in two geopolitical regions of the continent, namely the EU East and the EU west. We found that, the 2015 refugee crisis sparked different attitudinal reaction between these regions related to immigration, with trust in domestic and EU institutions predicting much of attitudes toward migration. We tested our hypotheses with data from the 7th and 8th rounds of the European Social Survey.